Management of Cutaneous Squamous Cell Carcinoma (Clear Cell Variant) in Bovine - A Case Report - Prajapati, Ankit S; Chauhan, Prakash M; Raval, Samir H (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Tumors of the bovine gastrointestinal tract are rare, possibly because of the low age of the sample population (Bertone, 1990). Neoplasia in cattle carries a poor prognosis because of early adenocarcinoma metastasis and the high fatality of lymphosarcoma. Squamous cell carcinoma is the second most rude type of skin cancer, with basal cell carcinoma being the most common (Rinker et al., 2001). Squamous cell carcinoma has been documented in bovine (Musser et al., 1993). Clear-cell squamous cell carcinoma is a rare variant of squamous cell carcinoma, first described by Kuo (1980) as a skin tumor. The exact etiology is unclear, but ultraviolet radiation has been suggested as a possible cause in humans (Lawal et al., 2013). This report documents a case of cutaneous squamous cell carcinoma (clear cell variant) in perianal region of a cow and its successful surgical management.